'Walking in two worlds': A qualitative review of income management in Cape York. Issue 1 (26th July 2020) - Scott, John; Staines, Zoe; Higginson, Angela; Lauchs, Mark; Ryan, Vanessa; Zhen, Liuissa
Abstract: The Cape York Welfare Reform (CYWR) initiative aims to reduce 'passive dependence' on welfare and restore 'positive social norms' to revitalise cultural and social networks and support economic engagement in Indigenous communities in the Cape York Region of Australia. Critics of the initiative and, in particular, its income management (IM) policies have associated it with a broader neoliberal reform agenda that delineates social 'problems' from their historical and structural context. This paper discusses key qualitative findings from a strategic review of CYWR, paying particular attention to the ways in which Cape York IM (CYIM) straddles both Indigenous and settler social norms, while perpetuating neoliberal conceptualisations of welfare 'dependency'. We situate these findings within the existing literature on Australia's other IM models and also consider them in relation to subsequent government responses to the review and associated policies. We argue that CYIM represents a unique initiative, the subtle nuances of which have been largely ignored or misunderstood by critics. Further, we conclude that any extension or revision of this initiative should be considered with respect to deep and wide‐ranging consultation of the Indigenous communities subject to CYWR. However, such consultation has not been the standard practice in Australian contexts. Abstract : The paper presents the qualitative findings of a Federal Government review of Cape York Income Management (CYIM). We argue that although CYIM shares a common ideological foundation with Australia's other IM policies, it is also distinct from these alternative forms of IM, particularly in terms of its evolution, high‐level of targeting, and delivery mechanism.